The Influence of Village Fund Allocation Policies on Infrastructure Development in Villages - Ade Irawan (Universitas Sultan Ageng Tirtayasa, 2023)
The objective of this study is to assess the impact of village fund allocation policies on infrastructure development in the village. This research was conducted by collecting data from respondents consisting of representatives from the village administration, community institutions, and communities involved in the development of village infrastructure. In the Manyeti village of Dawuan District, Subang Province. Utilizing a questionnaire, the procedure used is qualitative and collects data. To determine the impact of village fund allocation policy variables on village infrastructure development, a straightforward linear regression technique was utilized to analyze the data. The findings of the study indicate that village fund allocation policies have a substantial impact on infrastructure development in villages. It was discovered that infrastructure development in a village improved proportionally to the amount of funds allocated for infrastructure development. This research is anticipated to aid in the development of more effective and efficient village fund allocation policies for infrastructure development. In addition, the findings of this study can serve as a foundation for future research on infrastructure development in rural communities.